Social Criticism in Wa Mangku and Wa Buliga Folklore: A Literary Sociology Study - Muhidar, Muhidar; Mansyur, Firman Alamsyah; Arsad, Arsad (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study explores the role of local folklore as a medium for expressing social criticism, focusing on the folktales Wa Mangku and Wa Buliga from South Buton, Southeast Sulawesi. While previous studies often emphasize folklore’s cultural and educational value, limited attention has been given to its function in critiquing injustice. Using a qualitative descriptive method and a literary sociology approach, the research analyzes data obtained through document analysis and interviews with native informants from Burangasi Village. Thematic content analysis reveals various forms of social criticism, including environmental degradation, poverty, social stigma, abuse of power, spiritual manipulation, and unjust traditional practices. The Wa Mangku tale critiques authoritarian customs and societal passivity toward injustice, while Wa Buliga highlights slander, violence, and discrimination driven by collective prejudice. Both stories serve as cultural mirrors that reflect the lived experiences of marginalized individuals and the consequences of irrational tradition. The findings underscore folklore’s potential as a transformative educational tool for promoting social awareness and critical thinking. This research contributes to the discourse on oral literature as a means of fostering empathy, moral reflection, and civic consciousness within local communities.